Walking the tightrope of justifiable decision‑making: An exploratory qualitative study identifying barriers and solutions to efficient safety reporting - Jemima Thompson; Macey L. Murray; Matthew R. Sydes; Annabelle South; Sharon B. Love (PLoS ONE, 2026)
Background Safety reporting is integral to clinical trial conduct, aiming to protect the rights and safety of trial participants and future patients. Over time, reporting safety events has become increasingly complex, leading to inefficiencies which place extra burden on trial staff and potentially impact patient safety. Attempts have been made to streamline these processes. However, effecting change in practice is challenging. Changes to UK trial regulations introduced in 2025 may reduce inefficiencies. To incorporate these changes effectively, we need to understand what barriers exist for their implementation. This study aimed to identify barriers and solutions to efficient safety reporting processes from the perspective of staff working at registered academic trials units in the UK, with a view to developing recommendations to enable the delivery of more efficient safety reporting practices. Method This was an exploratory, observational, qualitative focus group study of trials unit staff across the UK. Verbatim transcripts of the focus group discussions were analysed using Reflexive Thematic Analysis. Results Twenty-three CTU staff participated in four focus groups. One over-arching theme was generated from the analysis, “ Walking on a tightrope: Making justifiable decisions”. Participants felt that they were performing a balancing act between efficient, risk-proportionate safety reporting and risk-aversion. Possible solutions included clarification of expectations and improved transparency, and improved training and knowledge building. Discussion Despite efforts to streamline safety reporting processes, problems persist with the implementation of risk-proportionate approaches. Concerns that decisions will be deemed inadequate and impact patient safety and well-being make decision-making a difficult balancing-act. Confident decision-making by trial practitioners can be facilitated through access to resources and training provided by regulators, supported by tools and case studies. Trials unit level actions, such as mentoring schemes or platforms to share knowledge and learning, can support knowledge building and confidence development.